Analysis of Translation Quality of An Illustrated Children Storybook Berjalan-Jalan Bersama Mama - Fivi Ariana Faizin; Muhammad Zaki Pahrul Hadi (STKIP Taman Siswa Bima, 2025)
Translation quality refers to how accurately, fluently, and appropriately a translated text conveys the meaning, tone, and intent of the original (source) text in the target language. High translation quality ensures that the target audience receives the message as intended, without confusion, distortion, or loss of meaning. The primary objective of this study is to evaluate the quality of translated children's storybooks from English into Indonesian. This research adopts a qualitative method by analyzing available data sources using a translation quality assessment instrument based on the model developed by Nababan et al. The data were obtained from storybooks published on the official website of the Language Development and Fostering Agency, and their translations were examined using the TQA model. The study aims to assess the translation quality in terms of accuracy, acceptability, and readability in accordance with the TQA framework. The findings reveal a considerable discrepancy between the translation from the perspective of the source language and that of the target language. These results underscore the importance of applying the TQA model to assess translation quality in order to produce natural and acceptable translations in the target language.